Mentalidades de estudiantes costarricenses para el estudio del inglés - Barquero, Luis (2019)
This study consists of a quantitative analysis comparing the mindsets of high school students from three different regions of Costa Rica. The objective is to identify students’ mindsets for English learning. Possible differences between the three geographical areas are explored. The results suggest that the students in all three regions appear to tend toward the growth mindset for studying English. No salient differences regarding students’ mindsets toward learning English were found among the three regions. The reasons for these results and pedagogical implications are also discussed.